2020
DOI: 10.3389/fpls.2019.01703
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Reverse Genetic System for Beet Necrotic Yellow Vein Virus to Study Rz1 Resistance Response in Sugar Beet

Abstract: Beet necrotic yellow vein virus (BNYVV) is causal agent of rhizomania disease, which is the most devastating viral disease in sugar beet production leading to a dramatic reduction in beet yield and sugar content. The virus is transmitted by the ubiquitous distributed soil-borne plasmodiophoromycete Polymyxa betae that infects the root tissue of young sugar beet plants. Rz1 is the major resistance gene widely used in most sugar beet varieties to control BNYVV. The strong selection pressure on the virus populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 52 publications
4
31
0
Order By: Relevance
“…Galein et al (2018) examined the variability and pathogenicity of BNYVV isolates from an area containing A-, B-and P-types, and found that P-type virus (with RNA5) showed the highest aggressiveness, although there is the complexity of genome reassortments between different types of BNYVV strains. Furthermore, Liebe et al (2020) showed that the presence of P-type RNA5 in the background of the A-type virus clone increased virus accumulation in the resistant plants, suggesting that this P-type RNA5 is involved in Rz1-RB. The present study here has provided more definite evidence on the effect of RNA3 and RNA5 on virus accumulation levels in Rz1-RB.…”
Section: Discussionmentioning
confidence: 98%
“…Galein et al (2018) examined the variability and pathogenicity of BNYVV isolates from an area containing A-, B-and P-types, and found that P-type virus (with RNA5) showed the highest aggressiveness, although there is the complexity of genome reassortments between different types of BNYVV strains. Furthermore, Liebe et al (2020) showed that the presence of P-type RNA5 in the background of the A-type virus clone increased virus accumulation in the resistant plants, suggesting that this P-type RNA5 is involved in Rz1-RB. The present study here has provided more definite evidence on the effect of RNA3 and RNA5 on virus accumulation levels in Rz1-RB.…”
Section: Discussionmentioning
confidence: 98%
“…The nucleotides at this location are considered to be among the most hypervariable within all eukaryotic viruses [ 25 , 34 , 43 ], a feature observed in our own recent study [ 17 ]. Moreover, recent associative [ 16 , 17 , 34 ] and functional [ 5 , 44 ] evidence suggests that variability in this region may account for the ability for some strains of the virus to circumvent dominant resistance genes in the sugar beet crop. As additional cases exist where a specific tetrad has been observed in both Rz-gene controlled and Rz-gene breaking isolates (e.g., tetrad ACHG [ 17 ]), it is possible that other changes in the genome may operate in conjunction with mutations in the tetrad motif or independent of this element in compromising host resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The two largest RNAs of the BNYVV genome, RNAs 1 and 2, collectively represent over 70% of the virus genome and encode the replication, packaging, cell–cell movement, and silencing suppression functions of the virus. In contrast to most other biologically-active clones of BNYVV that provide infection through transient genome transcription consequent to Agrobacterium infiltration (i.e., “agro-infection”; [ 44 , 45 , 46 ]), we chose to employ in vitro production of capped RNA transcriptions as the means to produce inoculum for the infection in recipient cells in a manner more consistent with that found in nature. Along with previous reports of others who used NGS data in the construction of clones from which infectious RNA was produced either through in vitro transcription or via agro-infection [ 47 ], our study validates this approach in constructing clones for the study of BNYVV.…”
Section: Discussionmentioning
confidence: 99%
“…Severe disease symptoms are the reduced size of the roots and typical constrictions (funnel or ‘wineglass’‐like shape) of the infected taproots sometimes with nodules (small tumorous growths) along the taproot. Necrosis of vascular tissues (Figure 1) (Liebe et al., 2020) starting with a pale yellow to dark brown discoloration and necrotic rings may also occur. In less heavily infested plants, symptoms may affect only one lateral root of the plant (McGrann et al., 2009; Rush et al., 2006; Neher and Gallian, 2014; EPPO, 2006).…”
Section: Pest Categorisationmentioning
confidence: 99%